Nutritional ingredients from spent brewer's yeast obtained by hydrolysis and selective membrane filtration integrated in a pilot process - Amorim, Manuela; Pereira, Joana O.; Gomes, David; Pereira, Carlos Dias; Pinheiro, Hélder; Pintado, Manuela (Journal of food engineering, 2016)
Spent brewer's yeast is a natural surplus from brewing industry. In order to up-grade this by-product, isolation of compounds has been tentatively assessed. The main objective of this work focuses on the use of ultrafiltration and nanofiltration pilot system for recovering cell compounds. Initially, yeast was autolyzed and ultrafiltered with a 10 kDa cut-off, and the two fractions obtained were hydrolyzed with Cynara cardunculus extract and nanofiltered with 3 kDa cut-off. Four fractions with different molecular weights were obtained, with protein and sugar contents ranging between 30–69% and 20–48%, respectively. Sodium and potassium were the major minerals present, whereas glutamine, glutamic acid and alanine, the most representative free amino acids. Peptide profile showed peptides with hydrophilic and hydrophobic characteristics, usually associated with biological activities, including antihypertensive and antioxidant. Thus, based on their compositions, all fractions show technological and biological potential, and can be used as nutritional ingredients in food and feed. •Selective membrane filtration pilot process for recovery spent brewer's yeast.•Four hydrolyzed fractions with different molecular weights with improved chemical and nutritional richness was obtained.•Ingredients for food supplements with biological properties.•Extracts can also be used for flavor technological purposes due to their mineral and amino acids content.